Simulating the mid-Pliocene Warm Period with the CCSM4 model - N. A. Rosenbloom; B. L. Otto-Bliesner; E. C. Brady; P. J. Lawrence (Geoscientific Model Development, 2013)
This paper describes the experimental design and model results from a 500 yr fully coupled Community Climate System, version 4, simulation of the mid-Pliocene Warm Period (mPWP) (ca. 3.3–3.0 Ma). We simulate the mPWP using the "alternate" protocol prescribed by the Pliocene Model Intercomparison Project (PlioMIP) for the AOGCM simulation (Experiment 2). Results from the CCSM4 mPWP simulation show a 1.9 °C increase in global mean annual temperature compared to the 1850 preindustrial control, with a polar amplification of ~3 times the global warming. Global precipitation increases slightly by 0.09 mm day−1 and the monsoon rainfall is enhanced, particularly in the Northern Hemisphere (NH). Areal sea ice extent decreases in both hemispheres but persists through the summers. The model simulates a relaxation of the zonal sea surface temperature (SST) gradient in the tropical Pacific, with the El Niño–Southern Oscillation (Niño3.4) ~20% weaker than the preindustrial and exhibiting extended periods of quiescence of up to 150 yr. The maximum Atlantic meridional overturning circulation and northward Atlantic oceanic heat transport are indistinguishable from the control. As compared to PRISM3, CCSM4 overestimates Southern Hemisphere (SH) sea surface temperatures, but underestimates NH warming, particularly in the North Atlantic, suggesting that an increase in northward ocean heat transport would bring CCSM4 SSTs into better alignment with proxy data.